Validitas Asesmen Diagnostik Kognitif Berbantuan Quizizz Pada Pembelajaran Pendidikan Pancasila di Sekolah Dasar - Kaifiyatus Syahroh; Reinita Reinita (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
The research was carried out due to several reasons, including the lack of differentiated learning according to the needs and competencies of each student. The aim of this research is to create differentiated learning to suit the abilities and competencies of each student by creating a cognitive diagnostic assessment assisted by quizizz in Pancasila education learning in class IV elementary school. This type of development research uses the ADDIE development model which consists of three stages in this research, namely Analysis, Design and Development. The data collection method used in this research is a validation questionnaire given to expert validators (material, language and assessment)to determine the validity of the cognitive diagnostic assessment product being developed. This research can produce valid cognitive diagnostic assessment products that are tested by expert validators. So it can be concluded that the cognitive diagnostic assessment assisted by quizizz in learning Pancasila education in grade IV elementary schools is valid and worthy of being tested in the field.